TPACK COMPETENCE AMONG PRE-SERVICE ENGLISH TEACHERS IN THE ERA OF THE MERDEKA CURRICULUM: A MIXED-METHODS STUDY AT AN INDONESIAN LPTK - Roza Susanti; Dwi Settya Mahaputri; Ifna Nifriza; Indah Rahmalia; Afdaleni Afdaleni (ELP (Journal of English Language Pedagogy), 2026)
The Merdeka Curriculum has intensified demands on Indonesian teacher education institutions (LPTK) to prepare pre-service English teachers capable of integrating technology meaningfully into learner-centered classrooms. However, no empirical study has yet examined TPACK development within a regional LPTK explicitly operating under Merdeka Curriculum mandates. This study investigated the TPACK competence levels of pre-service English teachers at STKIP Yayasan Abdi Pendidikan Payakumbuh and examined how the institution's preparation program addresses the demands of the Merdeka Curriculum. An explanatory sequential mixed-methods design was employed: 62 students completed an adapted TPACK questionnaire (? = 0.89), while eight students and four lecturers served as qualitative informants through semi-structured interviews. Additionally, 16 lesson plans were analyzed using a rubric adapted from Harris et al. (2010). The overall TPACK mean score was 3.47 (SD = 0.52), categorized as high, yet foundational domains (CK, M = 3.89; PK, M = 3.76) scored substantially higher than integrative domains (TCK, M = 3.18; TPACK, M = 3.05). Qualitative findings revealed three barriers: limited technology-integrated microteaching practice, curricular misalignment with Merdeka Curriculum principles, and low student self-efficacy in selecting pedagogically appropriate digital tools. These findings suggest that while foundational knowledge is adequately developed, purposeful technology integration remains underdeveloped. The study recommends TPACK-based curriculum mapping, redesigned microteaching with design-teach-reflect cycles, and systematic reflective practice aligned with Merdeka Curriculum principles.